THE ROLE OF CRITICAL THINKING IN ACADEMIC SKILLS, BUSINESS, AND SUCCESS - Navruzbek Jumayev; Mamura Narimanovna Kushakova (European Science Publishing, 2025)
The article analyzes the role of critical thinking in academic skills and business, particularly marketing and management, and examines mistakes associated with critical thinking in success.
Keywords: Critical thinking, cognitive impairment, survival effect, Abraham Weltz.